2022
DOI: 10.1038/s41380-022-01709-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in individuals of European and African ancestry and multi-trait analysis of opioid use disorder identifies 19 independent genome-wide significant risk loci

Abstract: Despite the large toll of opioid use disorder (OUD), genome-wide association studies (GWAS) of OUD to date have yielded few susceptibility loci. We performed a large-scale GWAS of OUD in individuals of European (EUR) and African (AFR) ancestry, optimizing genetic informativeness by performing MTAG (Multi-trait analysis of GWAS) with genetically correlated substance use disorders (SUDs). Meta-analysis included seven cohorts: the Million Veteran Program, Psychiatric Genomics Consortium, iPSYCH, FinnGen, Partners… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…For such SNPs, MTAG could have false positives in the first trait [14]. This statement is consistent with a recent study on opioid use disorder, which showed that increased detection of MTAG might come with the loss of specificity [16]. In our analyses, some of the newly identified loci by MTAG were verified to be shared between AUD and smoking behaviors by colocalization, such as rs6589386 on DRD2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For such SNPs, MTAG could have false positives in the first trait [14]. This statement is consistent with a recent study on opioid use disorder, which showed that increased detection of MTAG might come with the loss of specificity [16]. In our analyses, some of the newly identified loci by MTAG were verified to be shared between AUD and smoking behaviors by colocalization, such as rs6589386 on DRD2.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Wu et al utilized a sample size of approximately 60,000 EA individuals and identified genetic variants on seven genes commonly associated with four out of the following five psychiatric disorders: schizophrenia, bipolar disorder, autism spectrum disorder, attention-deficit hyperactivity disorder, and depression [15]. Recently, Deak et al applied MTAG to discover novel risk loci for opioid use disorder [16], and Xu et al applied MTAG for four common substance use disorders and reported several novel loci for opioid use disorder, cannabis use disorder, alcohol and smoking behaviors [17]. These studies show that MTAG is a useful method for identifying loci associated with strongly correlated psychiatric disorders, including substance use behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, no lead variants in the shared loci for OUD and psychiatric disorders, had a p-value <0.05 in the independent AA GWAS dataset on OUD 21 . A total of four of the OUD risk loci identified by conjFDR were identified in recent larger GWAS on OUD, specifically the PPP6C 42 , NCAM1 39 , DRD2 39 and FURIN 39,42,43 loci, supporting the validity of the results.…”
Section: Resultssupporting
confidence: 65%
“…It has previously been associated with SCZ 40 , BD 27 and MD 41 . This locus was not identified in the original OUD GWAS 21 , but reached genome-wide significance in subsequent GWAS on OUD, validating this finding 39,42,43 . The lead SNP rs4702 is shown to influence the expression of its nearest gene FURIN in neurons derived from human induced pluripotent stem cells, and influence synaptic function in synergy with other SCZ risk variants 50 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation